Longitudinal incidence and prevalence of adverse outcomes of diabetes mellitus in elderly patients. - Bethel, M; Sloan, F; Belsky, D; Feinglos, M (2007)
BACKGROUND: The natural history of type 2 diabetes mellitus (DM) in the elderly has not been previously described in a national longitudinal sample. METHODS: This national longitudinal analysis (January 1, 1991, to December 31, 2004) examines mortality and morbidity rates in a representative sample of elderly patients newly diagnosed as having DM. Medicare beneficiaries diagnosed as having DM in 1994 (n=33,772) were compared with a control group (n=25,563) regarding death, lower extremity complications, nephropathy, retinopathy, cardiovascular complications, and cerebrovascular complications. RESULTS: The DM group had excess mortality of 9.2% by year 11 compared with the control group. By 2004, 91.8% of the DM group experienced an adverse complication compared with 72.0% of the control group. The DM group had a higher prevalence and incidence of microvascular and macrovascular complications at all time points compared with controls. Patients with DM were at increased risk for all lower extremity complications, particularly those requiring surgical intervention (gangrene, debridement, and amputation). Cardiovascular complications were a leading cause of morbidity, with 57.6% of the DM group diagnosed as having heart failure compared with 34.1% of the controls. CONCLUSION: Elderly persons newly diagnosed as having DM experienced high rates of complications during 10-year follow-up, far in excess of elderly persons without this diagnosis, implying a substantial burden on the individual and on the health care system.